PENERAPAN METODE OPEN VPN-ACCESS SERVER SEBAGAI RANCANGAN JARINGAN WIDE AREA NETWORK PADA PADA PT. KOPEGTEL MEDIATRON - Muhammad Hasbi; Mohammad Badrul (Jurnal Techno Nusa Mandiri, 2014)
The development of information technology has developed rapidly from year to year. The use of the Internet as a very useful addition to mediation communications but still has weaknesses in its security. PT. Kopegtel Mediatron an official cooperation PT.Telekomunikasi Indonesia, Tbk. can not be separated from the network and use the internet to Operational constraints company faced the Kopegtel officials who are also working well as Telkom employees to obtain the necessary data as a report must come directly to the office, this way is not very effective. Solutions that can be used for this problem is to build a network Wide Area Network (WAN) technology with a Virtual Private network applications that can use OpenVPN Access Server. OpenVPN Access Server delivers ease and security in forming a network of virtual private network.